Removal of COD, BOD, and Detergent from Laundry Wastewater Using Coconut-Shell Activated Carbon in Batch and Continuous Fixed-Bed Adsorption - Alexander Tunggul Sutan Haji; Mujaroh Khotimah; Putri Setiani; Amelia Gultom; Ichi Fiaqi Hamada; Abentin Estim; Wisnu Prayogo (International Journal of Hydrological and Environmental for Sustainability, 2026)
Laundry wastewater contains high organic matter and detergent residues that may degrade the receiving water quality if discharged without treatment. This study investigated the performance of coconut-shell activated carbon for reducing chemical oxygen demand (COD), biochemical oxygen demand (BOD), and detergent concentration in laundry wastewater, using batch and continuous fixed-bed adsorption systems. Four activation treatments were evaluated at the batch stage: no activation, NaOH 0.2 N, HCl 0.1 N, and sequential NaOH 0.2 N–HCl 0.1 N. The best activator was then applied in a continuous upflow column with adsorbent thicknesses of 15, 20, and 25 cm. HCl 0.1 N produced the highest batch removal efficiencies, reaching 73.30% for COD, 71.53% for BOD, and 75.73% for detergent. Adsorption equilibrium for all parameters was better described by the Freundlich model than by the Langmuir model, indicating adsorption on a heterogeneous carbon surface. In the continuous system, the 25 cm bed showed the highest concentration-based removal, reaching 97.12% for COD, 97.03% for BOD, and 99.66% for detergent, and provided the longest breakthrough delay. However, the 20 cm bed yielded the highest average pollutant-load reduction, indicating a more balanced operational performance. Hydraulic conductivity decreased from 0.000058 to 0.000036 m/s during operation, suggesting progressive pore blockage and adsorbent saturation. These results demonstrate that coconut-shell activated carbon has good potential as a simple and practical adsorbent for decentralized laundry wastewater treatment.